The effect of foreign reinvestment and financial reporting incentives on cross-jurisdictional income shifting - Kenneth Klassen; Stacie Laplante (Contemporary Accounting Research, 2012)
This paper investigates the influence of foreign reinvestment-related and financial reporting incentives on income shifting of U.S. multinational companies.  While foreign and domestic policymakers are concerned with the effect of income shifting on dwindling tax revenues, to date no research has focused on the character of firms that are more aggressive income shifters. We provide insights on the role of cross-sectional variation in foreign reinvestment-related incentives and financial reporting incentives in income shifting; insights that are useful to policymakers, regulators, researchers and stakeholders. Using a comprehensive approach to estimate income shifting, we find evidence consistent with our argument that foreign reinvestment-related incentives affect a firm’s propensity to shift income when domestic tax rates exceed foreign tax rates, but not when foreign tax rates exceed domestic tax rates.  We also find that firms with low foreign tax rates and incentives to manage income on their financial statements more actively shift income out of the U.S. than other firms.  Finally, we estimate that firms with high reinvestment-related (financial reporting) incentives shift approximately $42 million ($43 million) of additional income per firm per year out of the U.S. relative to firms with low reinvestment-related (financial reporting) incentives.